Fulfilling the Accessibility Rights of Children with Special Needs: An Analysis of Facility Management in Early Childhood Islamic Education - Rohmatun Lukluk Isnaini; Sigit Purnama (Jurnal Pendidikan Anak Usia Dini Undiksha, 2025)
Kindergartens play an important role in ensuring accessibility for all children, including children with special needs (CSN). However, limited facilities and institutional readiness often hinder inclusive education implementation. This study aims to analyze how facility management supports accessibility for CSN in early childhood education institutions. This study employed a qualitative approach with a case study design. The research participants consisted of six teachers and two parents who were directly involved in the educational process of children with special needs. Data were collected through semi-structured interviews and observations using an interview guideline instrument covering five main themes: availability of learning facilities, utilization of educational technology, social learning activities, challenges in providing facilities, and parental expectations. The data were analyzed using thematic analysis through processes of coding, theme categorization, and interpretation of findings. The results indicate that the available facilities support motor development, the use of audio-visual learning media, and social interaction through role-playing activities. However, limitations in specialized support staff and the utilization of educational technology remain significant challenges in implementing inclusive services. The study concludes that inclusive educational practices can develop adaptively within non-inclusive institutions through flexible leadership and active parental involvement. These findings highlight the importance of strengthening teacher competence, providing professional support staff, and establishing more systematic policy support to expand inclusive education in early childhood education.